Low-intensity parent- and clinician-delivered support for young autistic children in Aotearoa New Zealand: a randomised controlled trialResearch in context - Hannah Waddington; Phoebe Jordan; Matthew Hammond; Jessica Tupou; Lee Patrick; Ella Macaskill; Georgia Davies; Sarah Pillar; Larah van der Meer; Andrew J.O. Whitehouse (Elsevier, 2024)
Summary: Background: Aotearoa New Zealand does not provide publicly-funded intensive autism support. While parent-mediated supports are promising, children and families may also benefit from direct clinician support. We tested the efficacy of a low-intensity programme involving parent- and clinician-delivered support for autistic children. Methods: This single-blind, two-arm randomised controlled trial assessed outcomes of a six-month low-intensity parent- and clinician-delivered support (2-3 h per week) based on the Early Start Denver Model compared to a control group who received monthly support calls and assistance with referrals. Children aged 1-4.5 years who were autistic or showing signs of autism and their parents were randomised to the low-intensity or control group by a blinded statistician using the Urn minimisation method. Assessments were conducted at baseline and immediately following the support period (24-weeks post-baseline). The primary outcome was child engagement during an interaction with their parent. The trial was pre-registered with ANZCTR: U1111-1260-2529. Findings: From March 2021 to May 2023, 56 families were randomised to either the low-intensity or control group. Following drop-outs, 21 families in the low-intensity group and 24 in the control group were included in analysis. There was large and significantly greater improvement in children's engagement in the low-intensity group compared to the control group (F (1, 43) = 21.47, p < 0.0001, ηp2 = 0.33). There was one recorded adverse event unrelated to the support and two adverse effects related to the support. Interpretation: A low-intensity parent- and clinician-delivered support can improve engagement between an autistic child and their parent during play. Low-intensity supports may be beneficial in areas where access to clinical autism supports is limited. Funding: Emerging Researcher First Grant from the Health Research Council of New Zealand.